Worldwide Prevalence of mcr-mediated Colistin-Resistance Escherichia coli in Isolates of Clinical Samples, Healthy Humans, and Livestock—A Systematic Review and Meta-Analysis - Carlos Bastidas-Caldes; Jacobus H. de Waard; María Soledad Salgado; María José Villacís; Marco Coral-Almeida; Yoshimasa Yamamoto; Manuel Calvopiña (Pathogens, 2022)
Background: Antimicrobial resistance is a serious public-health problem throughout the world. Escherichia coli, the most common Gram-negative microorganism, has developed different resistance mechanisms, making treating infections difficult. Colistin is considered a last-resort drug in the treatment of infections caused by E. coli. Plasmid-mediated mobile-colistin-resistant (mcr) genes in E. coli, now disseminated globally, are considered a major public-health threat. Humans, chickens, and pigs are the main reservoirs for E. coli and the sources of antibiotic resistance. Hence, an up-to-date and precise estimate of the global prevalence of mcr resistance genes in these reservoirs is necessary to understand more precisely the worldwide spread and to more effectively implement control and prevention strategies. Methodology: Publications were identified in the PubMed database on the basis of the PRISMA guidelines. English full-text articles were selected from December 2014 to March 2021. Descriptive statistics and a meta-analysis were performed in Excel and R software, respectively. Colistin resistance was defined as the molecular-genetic detection of the mcr genes. The crude and estimated prevalence were calculated for each host and continent. The studies were divided into two groups; community-based when they involved isolates from healthy humans, chickens, or pigs, and clinical studies when they involved only hospital, outpatient, or laboratory isolates. Results: A total of 1278 studies were identified and 218 were included in this systematic review and meta-analysis, divided into community studies (159 studies) and clinical studies (59 studies). The general prevalence of mcr-mediated colistin-resistant E. coli (mcrMCRE) was 6.51% (n = 11,583/177,720), reported in 54 countries and on five continents; Asia with 119 studies followed by Europe with 61 studies registered the most articles. Asia reported the major diversity of mcr-variants (eight of nine, except mcr-2). Worldwide, chickens and pigs proved to be the principal reservoir of mcr with an estimated prevalence of 15.8% and 14.9%, respectively. Healthy humans and clinical isolates showed a lower prevalence with 7.4% and 4.2% respectively. Conclusions: In this systematic review and meta-analysis, the worldwide prevalence of mcr in E. coli isolated from healthy humans, chickens, and pigs was investigated. A wide prevalence and distribution of mcr genes was demonstrated on all continents in E. coli isolates from the selected reservoirs. Understanding the epidemiology and occurrence in the reservoirs of mcr in E. coli on different continents of the world facilitates tracing how mcr genes are transmitted and determining the infection risks for humans. This knowledge can be used to reduce the incidence of zoonotic transmission by implementing the appropriate control programs.